Mood and Aspect in Spanish L2 and L3: Positive Transfer and Intercomprehension in British Education - Lourdes Barquín Sanmartín (Bellaterra Journal of Teaching & Learning Language & Literature, 2025)
This article presents a transdisciplinary doctoral study at the intersection of second and third language acquisition and foreign language pedagogy in British Higher Education. It investigates the common language sequence among British students: English (L1), French (L2), and Spanish (L3). The study offers a quantitative, yet descriptive comparison of native English speakers enrolled in Hispanic Studies at the University of Edinburgh, distinguishing between students of Spanish only (Spanish L2 group) and of both French and Spanish (Spanish L3 group). Findings reveal that the L3 group demonstrates higher proficiency across A2, B1, and B1+ levels. This advantage is linked to positive transfer from French to Spanish—two typologically related Romance languages. The analysis focuses on mood selection (indicativo/subjuntivo) and aspectual contrast (imperfecto/indefinido), both absent in English. Pedagogically, the study advocates for fostering Intercomprehension competence in the classroom to enhance interlinguistic awareness and strategic use of positive transfer in language learning.